A Study on Opinion of Education for Adults in Greater Noida Knowledge Park - Harikrishnan , M.; Anjali; Bhatia, Umang; Tihal, Harshita; Manglotia, Loveleen (Integrated Journal for Research in Arts and Humanities, 2023)
Adult education is the practice of involving adults in well-organized activities that promote comprehension and learning. Individuals are constantly challenged to improve their knowledge, skills, abilities, and aptitudes throughout their lives. As a result, the primary goal of adult education is to help individuals develop an understanding of various concepts. When adults need to meet a need or achieve a desired goal, they develop motivation and interest in learning. The main purpose of this study is to examine the different attributes connected with the teaching and learning of adult learners.